2023
DOI: 10.7759/cureus.50949
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Bilirubin (ALBI) Score and Systemic Immune-Inflammation Indexes Used As Pretreatment Outcome Predictors in Patients With Pancreatic Ductal Adenocarcinoma Undergoing Robotic or Open Whipple Procedures: A Logistic Regression Analysis

Alejandro Mejia,
Elaina Vivian,
Jimmy Shah
et al.

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer (PC) in the United States. In patients with resectable PC, identification of pretreatment biomarkers before surgery can help in the decision-making process by weighing the benefits of neo-adjuvant therapy, surgical procedure, and adjuvant therapy. The purpose of this study was to determine if the albumin-bilirubin (ALBI) score and immune-inflammatory marker levels can be used in combination as pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Studies in cancer have demonstrated that bilirubin suppresses CD4+ T cell responses, impacting antitumor immunity. Albumin, reflecting nutritional status and inflammation, influences patient survival [22]. The NLR mirrors the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cancer have demonstrated that bilirubin suppresses CD4+ T cell responses, impacting antitumor immunity. Albumin, reflecting nutritional status and inflammation, influences patient survival [22]. The NLR mirrors the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR mirrors the tumor immune microenvironment. Research suggests that a particular neutrophil subpopulation may downregulate CD4+ T cell proliferation and activity [22]. These biomarkers hold promise for predicting outcomes and guiding HCC management.…”
Section: Discussionmentioning
confidence: 99%